Static Stress Simulation Analysis of Skid Frame of Portable Open Waste Container Using FEA Method on SolidWorks - Ulfah, Nurul; Adicita, Yosef; Ariyanto, Nugroho Pratomo; Puspita, Roza; Arifin, Nurul Laili; Wibowo, Ari; Putra, Rama Dani Eka (Journal of Engineering Science and Technology Management, 2025)
Portable open waste container is a traditional waste transport tool that is still widely used in various places. Skid frame is an important component in the construction of portable open waste container that serves to withstand static and dynamic loads during waste transport. Therefore, it is necessary to analyse the strength of the skid frame structure to ensure the design is able to withstand the given load. This research aims to analyse the stress distribution, deformation, and safety factor of the portable open waste container skid frame using the Finite Element Analysis method in Solidworks software. The analysis results show that the maximum stress that occurs in the skid frame is 249.921 MPa which almost reaches the yield stress of ASTM A36 steel material, which is 250 MPa, with a maximum deformation of 20.544 mm, and a minimum safety factor of 0.6. Based on these results, it can be concluded that the skid frame design needs to be optimised to improve the durability of the structure and safety during operation